Doris Lessing : border crossings - Lessing, Doris, 1919-2013 (Continuum literary studies., 2009)
Despite winning the Nobel Prize for Literature, Doris Lessing has received relatively little critical attention. One of the reasons for this is that Lessing has spent much of her lifetime and her long published writing career crossing both national and ideological borders. This essay collection reflects and explores the incredible variety of Lessing's border crossings and positions her writing in its various social and cultural contexts. Lessing crosses literal national borders in her life and work, but more controversial have been her crossings of genre borders into sci-fi and "space fiction."